STRATEGIES TO FULFILL FAMILY NEEDS IN SOCIOECONOMICALLY VULNERABLE WOMEN - Kardeti, Denti; Agiati, R. Enkeu; Widiowati, Didiet; Rusmana, Aep; Rustanto, Bambang; Irianti, Decky; Sari, Raysha Pamela (Universitas Padjadjaran, 2024)
This study aims to explore the strategies used by socioeconomically vulnerable women who are heads of low-income families to meet their family's needs. The research was conducted with four socioeconomically vulnerable women who are heads of low-income families in Pasanggrahan Village, Garut. The research data were collected through semi-structured interviews and observations from June-July 2023. The results showed that the participants used the same strategy template to fulfill the needs of their low-income families. Fulfilling economic needs is done by selling snacks in the market. Then, they save food to meet their daily needs and set aside a little money to fulfill other needs. They borrow from mobile banks when facing emergencies to fulfill daily expenses and trading capital and pay health costs when experiencing illnesses that must be treated. This strategy is carried out because the income generated by poor women's family heads or family members can only partially fulfill the family's basic needs. The poverty experienced by the participants was inherited from their families. However, this can be overcome by providing training to improve community entrepreneurship skills and competencies through utilizing village funds.